Biomechanical comparison of an intramedullary nail combined with a reconstruction plate combination versus a single intramedullary nail in unstable intertrochanteric fractures with lateral femoral wall fracture: A finite element analysis - Jun Zhang; Yan Wei; Guoding Li; Jian Wang; Baoqing Yu (Acta Orthopaedica et Traumatologica Turcica)
Objective: This study aimed to compare the biomechanical performance of an intramedullary nail combined with a reconstruction plate and a single intramedullary nail in the treatment of unstable intertrochanteric femoral fractures with a fracture of the lateral femoral wall (LFW).